Re-Greening Earth - Dickson Donald Despommier (Oz, 2009)
Throughout Earth’s history, climate change has been the driving force in evolution, selecting new life forms pre-adapted to those changes. But the rate of change we are now experiencing has been in fast forward mode for only the last 100 years or so.